Joint Action Enhances Cohesion and Positive Affect, but Suppresses Aspects of Creativity When Combined With Shared Goals - Mogan, Reneeta; Bulbulia, Joseph; Fischer, Ronald (Frontiers in Psychology, 2019)
We aimed to examine the link between behavioral synchrony and creativity (both divergent thinking and convergent thinking) using an established experimental paradigm. A secondary aim was to replicate and extend the amplified positive effects of shared intentionality (i.e., having a shared purpose) on social and affective responses. Participants (N = 138) were randomly assigned to move in synchrony, move in asynchrony, or passively observe others moving. To induce shared intentionality, participants were provided with either a group goal of working together or an individual goal of focusing on the individual participant’s own movements. First, our results revealed that synchrony reduces convergent thinking for group goals conditions (shared intentionality), but we found no support for differences in divergent thinking. Second, we replicated synchrony’s positive effect on cohesion and positive affect. These findings are consistent with evolutionary theories of group rituals as a means for inducing solidarity, and extend previous findings by showing that synchrony induces shared patterns of thought.